Relationship between papilla‐related variables and post endoscopic retrograde cholangiopancreatography pancreatitis: A multicenter, prospective study. Issue 12 (29th June 2020) - Wang, Xiangping; Zhao, Jianghai; Wang, Limei; Ning, Bo; Zeng, Wei; Tao, Qin; Ren, Gui; Liang, Shuhui; Luo, Hui; Wang, Biaoluo; Farrell, James J.; Pan, Yanglin; et al.
Abstract: Background and Aim: Papilla with hooknose or long protruding shape may increase the difficulty of cannulation during endoscopic retrograde cholangiopancreatography (ERCP). However, the relationship between papilla anatomy and complications of ERCP has not been fully understood. We aimed to investigate the effect of major duodenal papilla morphology on post‐ERCP pancreatitis (PEP) and the procedure of cannulation. Methods: Patients with native papilla who underwent ERCP were recruited to this multicenter study. Papilla‐related variables were collected, including the length of long axis (L), short axis (S) and opening width (OW), transverse fold, periampullary diverticulum (PAD), papilla location, orientation, swelling, and presence of duodenal stenosis. Demographic data and the procedure of cannulation were also prospectively evaluated. The primary outcome was PEP incidence. Multivariate analysis was used to identify high risk factors for PEP. Results: Six hundred and fifty‐eight patients were enrolled. Overall PEP incidence was 4.7% (31/658). The papilla of patients complicated with PEP had higher long to short axis (L/S) ratio (odds ratio [OR] 3.84, 95% confidence interval [CI]: 1.37–10.74, P = 0.010), higher long axis to opening width (L/OW) ratio (OR 1.35, 95%CI: 1.06–1.71, P = 0.014), more transverse folds (OR 2.53, 95%CI: 1.02–6.26, P = 0.044), and less periampullary diverticulum (OR 0.21, 95%CI: 0.06–0.70, P = 0.011). Multivariate analysis revealed that the indication of common bile duct stones, normal bilirubin, inadvertent pancreatic duct cannulation > 1, L/S ratio ≥ 1.5, and absence of PAD were independent risk factors for PEP. Conclusion: Besides patient‐related and procedure‐related factors, papilla‐related variables, such as L/S ratio and PAD, can be considered as a third type of factors associated with PEP (Clinicaltrials.gov number: NCT03550768).